PENDIDIKAN PLURALISME DALAM PERSPEKTIF GUS DUR DAN SYAFI’I MA’ARIF - Khoiruddin, Ahmad; Khalilurrahman; Prasetiya, Benny (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Gus Dur (KH Abdurrahman Wahid) and Syafi'i Ma'arif, as Muslim intellectuals who came from Nahdlatul Ulama and Muhammadiyah, had very valuable ideas, including in the context of pluralist education. Gus Dur and Syafi'i Ma'arif's perspective on pluralism education reflects a deep understanding and values such as tolerance, diversity and respect for differences in society. Here are some important aspects in both views. In Gus Dur's perspective, the main focus lies on tolerance and diversity. He emphasized the importance of equality and understanding religion as the foundation for a harmonious life. On the other hand, Syafi'i Ma'arif focuses on multicultural education and humanist education. Although there are differences in approach between the two, there are similarities in their views. These two figures have the common goal of avoiding conflict, as well as building awareness and integration of religious values in society. Thus, Gus Dur and Syafi'i Ma'arif's approach to pluralistic education creates a strong foundation for realizing social harmony and respect for diversity Keywords:  Pluralism Education; Gus Dur's Pluralism Education; Syafi'i Ma'arif's Pluralism Education.